From secondary alcohols to tertiary fluoro substituents: A simple route to hydroxymethyl branched sugars with a fluorine substituent at the branching point. (21st December 2016) - Schalli, Michael; Thonhofer, Martin; Wolfsgruber, Andreas; Weber, Hansjörg; Fischer, Roland; Saf, Robert; Stütz, Arnold E.
Abstract: From a secondary hydroxyl group, by the simple sequence of oxidation, Wittig reaction of the obtained ulose with methoxymethylene triphenyl phosphorane, exposure of the resulting exocyclic enol ether to Selectfluor and subsequent reduction of the α-fluoro aldehyde thus obtained, tertiary fluoro substituents can be introduced into carbohydrate and carbohydrate-related scaffolds at a branching point now bearing a new hydroxymethyl group. Graphical abstract: Highlights: Selectfluor converts exocyclic enol ethers (iso exoglycals) into branched chain sugars with tertiary fluoro substituents. The conversion is compatible with acid-sensitive protecting groups. This method is versatile, flexible and robust.